Elephant Speak : A Devoted Keeper's Life Among the Herd. - Crandall, Melissa (La Vergne : Ooligan Press, 2020)
Through the story of one man's extraordinary bonds with the elephants he cares for, Elephant Speak: A Devoted Keeper's Life Among the Herd shows that progress is possible when we accept our shortcomings and embrace conversation.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Henneous, Roger; Oregon Zoo (Portland, Or.); Oregon Zoo (Portland, Or.); Zoo keepers -- Oregon -- Biography; Gardiens de jardin zoologique -- Oregon -- Biographies; Zoo keepers; Oregon; Biographies